Postoperative radiotherapy for meningiomas – a decision-making analysis - Fischer, Galina Farina; Brügge, Detlef; Andratschke, Nicolaus; Baumert, Brigitta Gertrud; Bosetti, Davide Giovanni; Caparrotti, Francesca; Herrmann, Evelyn; Papachristofilou, Alexandros; Rogers, Susanne; Schwyzer, Lucia; Zwahlen, Daniel Rudolf; Hundsberger, Thomas; et al. (BMC cancer, 2022)
Background The management of meningiomas is challenging, and the role of postoperative radiotherapy is not standardized. Methods Radiation oncology experts in Swiss centres were asked to participate in this decision-making analysis on the use of postoperative radiotherapy (RT) for meningiomas. Experts from ten Swiss centres agreed to participate and provided their treatment algorithms. Their input was converted into decision trees based on the objective consensus methodology. The decision trees were used as a basis to identify consensus and discrepancies in clinical routine. Results Several criteria used for decision-making in postoperative RT in meningiomas were identified: histological grading, resection status, recurrence, location of the tumour, zugzwang (therapeutic need to treat and/or severity of symptoms), size, and cell division rate. Postoperative RT is recommended by all experts for WHO grade III tumours as well as for incompletely resected WHO grade II tumours. While most centres do not recommend adjuvant irradiation for WHO grade I meningiomas, some offer this treatment in recurrent situations or routinely for symptomatic tumours in critical locations. The recommendations for postoperative RT for recurrent or incompletely resected WHO grade I and II meningiomas were surprisingly heterogeneous. Conclusions Due to limited evidence on the utility of postoperative RT for meningiomas, treatment strategies vary considerably among clinical experts depending on the clinical setting, even in a small country like Switzerland. Clear majorities were identified for postoperative RT in WHO grade III meningiomas and against RT for hemispheric grade I meningiomas outside critical locations. The limited data and variations in clinical recommendations are in contrast with the high prevalence of meningiomas, especially in elderly individuals.